2022
DOI: 10.1108/pijpsm-10-2021-0141
|View full text |Cite
|
Sign up to set email alerts
|

The frequency and clustering of autism-related behaviors during encounters between the police and the autism community

Abstract: PurposeThis paper intends to examine the behaviors autistic individuals display during police encounters, determine if there are differences in those behaviors by age and gender, then examine if any behaviors cluster or frequently co-occur.Design/methodology/approachUsing data from the Survey of Parents and Caregivers of Individuals with autism spectrum disorder and focusing on a subsample of respondents who report that their autistic loved one has had prior police contact, the authors examine the frequency an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…, 2013; Vivanti and Rogers, 2014), such as gestures, body posture and eye contact. Additionally, scholars have shown that in police encounters, autistic individuals may have difficulty with back-and-forth communication and may communicate in a delayed or unusual manner (Wallace et al. , 2022).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…, 2013; Vivanti and Rogers, 2014), such as gestures, body posture and eye contact. Additionally, scholars have shown that in police encounters, autistic individuals may have difficulty with back-and-forth communication and may communicate in a delayed or unusual manner (Wallace et al. , 2022).…”
Section: Introductionmentioning
confidence: 99%
“…(2017) and Tint et al. (2017)), but few studies can speak to what happens inside an encounter (for exceptions, see Wallace et al. (2022) and Watson et al (2022)).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Next, using caregiver-reported information on the behaviors displayed during police encounters by individuals with ASD, Wallace et al. (2022) detail the most commonly occurring behaviors of individuals with ASD when interacting with police and conducted a cluster analysis to determine which behaviors typically co-occur.…”
Section: Inside Interactions Between the Police And Individuals On Th...mentioning
confidence: 99%